Issues of sustainability in the southern ocean fisheries ‚Äö - the case of the Patagonian Toothfish - Fallon, L; Elaine Stratford (2003)
The Southern Ocean is a hostile and remote marine environment. It is also a place of great beauty that contains unique fish, bird, mammal and coral species, and thousands of invertebrates, plants and micro-organisms ‚Äö - many of which we know little about or which are endemic and occur nowhere else in the world. The Southern Ocean also contains a wealth of natural marine resources that include the Patagonian toothfish (Dissostichus eleginoides) fishery. This fishery has come under increasing pressure over the last decade as fishers have harvested stocks to meet the demands of an increasing world population and an insatiable desire by consumers to eat white-fleshed fish (Fallon and Kriwoken submitted). Given the demand for Patagonian toothfish, illegal fishing of these stocks has flourished and the incidental mortality of seabirds in this longline fishery threatens many endangered albatross species. In addition, discarded longline equipment threatens marine mammals when they become entangled in the lines. This report focuses on issues of sustainability in the Southern Oceans fisheries, with specific reference to the Patagonian toothfish. The paper also informs a series of companion Internet sites that summarise the findings reported in detail here and they can be accessed at . A description of the Southern Ocean, and its physical and biological characteristics, sets the scene for a related discussion about its marine resources. We then outline the historical and contemporary context of the Southern Ocean's management, and elaborate on the range of fishing techniques used to harvest a number of fisheries. With this important background information in place, we examine the case of the Patagonian toothfish describing its ecology, stock estimates and commercial exploitation. An analysis of the incidence of illegal, unreported and unregulated (IUU) fishing then leads to a discussion of trade in Patagonian toothfish. What becomes clear from this work is that there are various international actors of influence whose ...